(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
In the present case report, a 58-year-old man consulted in the Outpatient department of Dayanand Ayurvedic College, Jalandhar. The complaint of the patient was recurrent skin rashes with redness, skin oedema, itching, flaking and discolouration in the skin. By examining the signs and symptoms, the patient was diagnosed with Eczema (Vicharchika), Shodhana and Shaman Chikitsa was given under the treatment of Vicharchika[1]. Vicharchika, according to Ayurveda, is a Raktapradoshaja Vyaadhi with the involvement of Tridoshas, and it is Kapha in predominance[2]. The patient was given Virechana Karma along with the local application of Japapatryadi tail and Amritadi kwath orally for a period of 2 months. After that, the condition of the patient was assessed on the basis of signs and symptoms of Vicharchika, which were cured after taking the treatment. This study shows that the cases of eczema (Vicharchika) can be successfully managed with Virechana Karma followed by Japapatryadi tail locally and Amritadi kwath given orally.